2013
DOI: 10.1089/cell.2013.0026
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Histone Deacetylase–Specific Isoforms Enhances Expression of Pluripotency Genes in Bovine Fibroblasts

Abstract: Histone deacetylases (HDACs) catalyze deacetylation of histones that results in altered transcriptional activity. Inhibitors of HDACs have been shown to induce transcriptional changes that contribute positively to reprogramming somatic cells either by nuclear transfer or inducing a pluripotent state. However, the exact molecular mechanisms whereby HDAC inhibitors function and the specificity of the HDAC isoforms in cell reprogramming are not yet fully understood. Herein, we report the ability of individual iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Similar to the results of our present study, in which TSA, a member of the family of non‐selective inhibitors of HDACs representing a class I (HDACs 1–3; HDAC8) and a class II (HDACs 4–7; HDAC9; HDAC10), was applied to impermanently block the biocatalytic activities of HDACs in nuclear donor BM‐MSCs, Staszkiewicz et al () have indicated that a transient downregulation of specific HDAC isoforms (via knocking down expression of target HDAC genes) with the aid of small interfering (si) RNA‐mediated transfection biases, to a large degree, the transcriptional activity of pluripotency‐related genes in bovine foetal fibroblast cell lines, leading to highly elevated Oct‐4 , Sox2 and Nanog mRNA levels on the day of their using for SCNT. De novo onset and enhancement of expression of three pluripotency‐related genes ( Oct‐4 , Sox2 and Nanog ) that had been arisen from a temporary selective silencing individual HDAC isoenzymes representing a class I (HDAC2), a class II (HDAC4; HDAC9) and a class III (SIRT3 sirtuin) seem to be a conditio sine qua non for triggering a pluripotent state and consequently improving reprogrammability of such epigenomically modulated nuclear donor cells in the cloned embryos generated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to the results of our present study, in which TSA, a member of the family of non‐selective inhibitors of HDACs representing a class I (HDACs 1–3; HDAC8) and a class II (HDACs 4–7; HDAC9; HDAC10), was applied to impermanently block the biocatalytic activities of HDACs in nuclear donor BM‐MSCs, Staszkiewicz et al () have indicated that a transient downregulation of specific HDAC isoforms (via knocking down expression of target HDAC genes) with the aid of small interfering (si) RNA‐mediated transfection biases, to a large degree, the transcriptional activity of pluripotency‐related genes in bovine foetal fibroblast cell lines, leading to highly elevated Oct‐4 , Sox2 and Nanog mRNA levels on the day of their using for SCNT. De novo onset and enhancement of expression of three pluripotency‐related genes ( Oct‐4 , Sox2 and Nanog ) that had been arisen from a temporary selective silencing individual HDAC isoenzymes representing a class I (HDAC2), a class II (HDAC4; HDAC9) and a class III (SIRT3 sirtuin) seem to be a conditio sine qua non for triggering a pluripotent state and consequently improving reprogrammability of such epigenomically modulated nuclear donor cells in the cloned embryos generated.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, we have shown that non‐specific blocking functions of HDACs by TSA results in considerable overexpression of a broad panel of pluripotency‐related genes in nuclear donor BM‐MSCs, suggesting especial hypersensitivity to actions of HDACs, histone acetyltransferases and HDAC inhibitors of histone lysine moieties within chromatin nucleosomal cores associated with Sox2 , Rex1 , c‐Myc and Nanog genes. Several studies have already confirmed that the lysine residues of histones H3 and/or H4 linked to Nanog gene turn out to be hypersensible to the regulatory functions of acetylation and deacetylation modifications (Hattori et al, ; Moon et al, ; Staszkiewicz et al, ). It is beyond any doubt that Nanog is thought to be one of the predominant transcriptional factors involved in the mechanisms underlying synergistic inter‐protein communication within the framework of Oct4‐Sox2‐Nanog transcriptional network that has been found to be inevitable to induce and maintain the cellular pluripotency and stemness properties (Moon et al, ; Sumer et al, ; Theunissen et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Inhibitors of HDACs have been shown to induce transcriptional changes that contribute positively to reprogramming somatic cells either by nuclear transfer or inducing a pluripotent state (Kretsovali et al, ). Recently Staszkiewicz et al () found that the silencing of HDACs through SiRNA upregulates the expression of pluripotency genes in bovine foetal fibroblasts. Reactivation of pluripotency genes such as Oct4, Nanog and Klf4 was also observed in neurosphere cells treated with TSA and azacytidine (AzaC) (Ruau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…But, the low cloning efficiency and reconstructed embryo dysplasia resulting from incomplete reprogramming of the donor nucleus are responsible for the slow pace of development in the field of porcine SCNT (Hill et al 2000;Yang et al 2007). Different studies have shown that the most important and effective way to promote epigenetic reprogramming of donor cell nuclei and restore their totipotency is to change the histone acetylation or DNA methylation status of somatic cell genome before and/or after its transplantation into a cytoplasm of enucleated recipient oocyte (Samiec et al 2012;Staszkiewicz et al 2013;Zhou et al 2014;Samiec et al 2015). Alone treatment of donor cells with different concentrations of FK228 for 24 h did not obviously improve the cleavage rate of cloned embryos.…”
Section: Discussionmentioning
confidence: 99%